The analysis of finite raising constructions in Ilami Kurdish - Karimipour, Amir; Sharifi, Shahla (Onomázein, 2023)
This paper is an attempt to investigate hyper-raising constructions in Ilami Kurdish (henceforth IK), a southern dialect of Kurdish, spoken in Iran. In particular, we aim to argue that these constructions, which involve the extraction of a DP out of a finite CP, represent an A-movement which ‘leaves behind a resumptive pro in the extraction position’ for assigning case-marking and further concord-agreement relations, the operation which was proposed by Ademola-Adeoye (2011) regarding hyper-raising, hyper-ECM and copy raising in language. Results show that IK permits subject-to-subject and also object-to-subject raising. The latter, with its effects on the matrix verb, has not been discussed so much in literature and is stipulated to be a language-specific feature found in IK. It seems safe to conclude that parametric analysis of IK raising structures might be more plausible instead of imposing a strict pattern of raising (definitely English-type pattern) on this dialect.